The Application of SIMAKEL Website Technology for Offline Class Booking - Sahara, Siti; Aulia, Erlisa; Mumtaz, Faiz Ilham (International Journal Software Engineering and Computer Science (IJSECS), 2024)
Education is a critical driver for the advancement of a nation's infrastructure, particularly through the application of information technology. At Universitas Negeri Jakarta, the limited availability of classrooms, due to ongoing infrastructure development, has posed significant challenges to the management of face-to-face teaching schedules. This study aims to develop the SIMAKEL (Siap Masuk Kelas) website as an efficient solution for managing classroom reservations. The research employs a Research and Development (R&D) approach using the ADDIE model, which includes five stages: analysis, design, development, implementation, and evaluation. The findings indicate that the SIMAKEL website effectively facilitates classroom management, minimizes scheduling conflicts, and allows for real-time monitoring of room availability. The implementation of this system is expected to enhance the structure and efficiency of academic activities, providing students with streamlined access to classroom usage information. User evaluations reflect a high level of satisfaction with the website's performance, demonstrating its effectiveness in supporting academic operations.